Strengthening Business Units (Catering, Fashion and Batik Units) Pesantren-Based - APRINDA, DEWI (Journal of Islamic Economy and Community Engagement, 2022)
This research is a qualitative research and the analysis used is descriptive which aims to optimize the existing business units in Pesantren Al Mumtaz, especially catering, fashion, and batik unit. Data collection techniques in the form of observation and interviews. The management carried out on each business unit is started with preparations and processes carried out so as to produce the expected outputs for each of these business units. Utilization of organizational resources strats from planning, organizing, arranging staf according to their fields of expertise so that they can professional management, controlled directing and supervision, will ensure the proper functioning of managerial processes. Keywords : Management, business units, Pesantren